Metastatic Uterine Leiomyosarcoma in a Nullipara with Primary Infertility: A Case Report - Anozie, Okechukwu B.; Nwafor, Johnbosco I.; Esike, Chidi U.; Ukaegbe, Chukwuemeka I.; Ewah, Richard L.; Onwe, Emeka O.; Eze, Justus N.; Asogwa, Sunday U. (International Journal of Innovative Research in Medical Science, 2019)
Uterine leiomyosarcoma accounts for 1-2% of uterine cancers. It is an extremely aggressive malignancy associated with a poor prognosis. Women affected may vary in age, but are most common between 4th and 7th decades of life. Presenting symptoms mimic uterine leiomyoma. Preoperative diagnosis of uterine leiomyosarcoma is difficult and often made at time of surgical resection. We report a case of Mrs A.E, a 40 year old nullipara with history of primary infertility of 20 years duration, who presented with abdominal swelling of 3 years and vaginal bleeding of 7 weeks duration. Abdominopelvic ultra-sonography done at presentation was suggestive of leiomyoma. She was scheduled for myomectomy and subsequently had total abdominal hysterectomy and omentectomy following intra-operative findings of features suggestive of leiomyosarcoma with evidence of metastasis to omentum. These findings were confirmed on histology of the specimen. She received one cycle of combination chemotherapy but was lost to follow up. Uterine LMS is an aggressive tumour, therefore, a high index of suspicion is needed especially for huge uterine nodules and such patients must be closely monitored for adequate management.